2003
DOI: 10.1046/j.1532-5415.2003.51103.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Multifaceted Intervention on Falls in Nursing Home Residents

Abstract: The incidence density rate of falls and fallers differed considerably between the control and intervention groups. The study was underpowered to demonstrate a significant difference of hip or nonhip fractures. Because of a low fracture rate in both groups, the investigation of fracture rates would have required a larger sample size to detect an effect of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
209
0
24

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(259 citation statements)
references
References 34 publications
(57 reference statements)
2
209
0
24
Order By: Relevance
“…19,[52][53][54][55][56] Furthermore, based on our results, exercise programs should last at least 3 months before a beneficial effect on falling can be expected. This compares favorably with the studies of Becker et al, 57 who found that intervention effect on falling became apparent only after 6 months of training, and of Wolf et al, 19 who reported effects after 4 months of training. It is observed that in these studies conclusions on time dependency were based on visual inspection and/or multiple comparisons, instead of demonstrating the time dependency by group by period interaction analyses.…”
Section: Discussionsupporting
confidence: 83%
“…19,[52][53][54][55][56] Furthermore, based on our results, exercise programs should last at least 3 months before a beneficial effect on falling can be expected. This compares favorably with the studies of Becker et al, 57 who found that intervention effect on falling became apparent only after 6 months of training, and of Wolf et al, 19 who reported effects after 4 months of training. It is observed that in these studies conclusions on time dependency were based on visual inspection and/or multiple comparisons, instead of demonstrating the time dependency by group by period interaction analyses.…”
Section: Discussionsupporting
confidence: 83%
“…Interventions combining education, environmental adaptations, balance/ resistance training, and hip protectors successfully reduced falls in 1 study 25 ; in another, a combination of exercise, visual, and counseling interventions showed some success in reducing falls 26 . Gillespie, Gillespie, and Robertson 27 reviewed 10 years of randomized trials of interventions designed to reduce falls in elderly patients.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the studies evaluating multifactorial interventions have been conducted in community settings and, in a number of cases, similar approaches in residential care settings have not been as successful. Multifactorial fall prevention measures do not appear to work in those attending hospital after a fall with cognitive impairment (101), but similar interventions in residential care facilities are effective (98,(107)(108)(109). It appears that interventions should not only be tailored to the individual but also to the particular setting.…”
Section: Cognitively Impaired Older People and Those In Residential Cmentioning
confidence: 99%
“…Residential care dwellers (58,59,82,98,99,(106)(107)(108)(109)110) In long-term care and residential care settings assessment for risk and appropriate multifactorial interventions for all residents (including those with dementia and cognitive impairment) there is some evidence to support: Exercise (83,87,89-98, 102,107 ) Specific exercise programmes work best within a multifactorial fall-prevention programme but there is evidence that they work alone as well.…”
mentioning
confidence: 99%